The Impacts Of Bullying On The Main Character In The Movie “Laal Singh Chadha” (2022) By Advait Chandan - Nada Rizqi Pratiwi; Abdillah Nugroho (Publikasi Indonesia, 2023)
In this study, the researchers identified the types of bullying and described the impact of bullying on the main character of the film Laal Sings Chaddha. The data in this study are in the form of words and actions that contain elements of bullying in the film Laal Sings Chaddha. This research was conducted by analyzing data qualitatively. The research findings show that there are three effects of bullying on the main character of the film Laal Sings Chaddha: low psychological well-being, poor adjustment, and psychological stress. Low psychological well-being is the most dominant impact of bullying in Carrie's film. There is one type of bullying found in the film Laal Sings Chaddha: physical bullying. Physical bullying is the most dominant type of bullying found in the film Laal Sings Chaddha.